The Chronicle in Latin America. The case of Etiqueta Negra - Szady, Beata (2015)
At the end of the 20th century, in Latin America, Gabriel García Márquez created the Foundation of New Latin American Journalism (FNPI). Thanks to this, a few years later, it shows the growth of the media, especially magazines that published chronicles. One of the most important exponents is the Peruvian magazine Etiqueta Negra. This article details the situation of the contemporary Chronicle in Latin America and a critical analysis of Etiqueta Negra.